Understanding the impact of the Covid-19 pandemic on delivery of rehabilitation in specialist palliative care services: An analysis of the CovPall-Rehab survey data. (February 2022) - Bayly, Joanne; Bradshaw, Andy; Fettes, Lucy; Omarjee, Muhammed; Talbot-Rice, Helena; Walshe, Catherine; Sleeman, Katherine E; Bajwah, Sabrina; Dunleavy, Lesley; Hocaoglu, Mevhibe; Oluyase, Adejoke; Garner, Ian; et al.
Background: Palliative rehabilitation involves multi-professional processes and interventions aimed at optimising patients' symptom self-management, independence and social participation throughout advanced illness. Rehabilitation services were highly disrupted during the Covid-19 pandemic. Aim: To understand rehabilitation provision in palliative care services during the Covid-19 pandemic, identifying and reflecting on adaptative and innovative practice to inform ongoing provision. Design: Cross-sectional national online survey. Setting/participants: Rehabilitation leads for specialist palliative care services across hospice, hospital, or community settings, conducted from 30/07/20 to 21/09/2020. Findings: 61 completed responses (England, n  = 55; Scotland, n  = 4; Wales, n  = 1; and Northern Ireland, n  = 1) most frequently from services based in hospices (56/61, 92%) providing adult rehabilitation. Most services (55/61, 90%) reported rehabilitation provision becoming remote during Covid-19 and half reported reduced caseloads. Rehabilitation teams frequently had staff members on sick-leave with suspected/confirmed Covid-19 (27/61, 44%), redeployed to other services/organisations (25/61, 41%) or furloughed (15/61, 26%). Free text responses were constructed into four themes: (i) fluctuating shared spaces; (ii) remote and digitised rehabilitation offer; (iii) capacity to provide and participate in rehabilitation; (iv) Covid-19 as a springboard for positive change. These represent how rehabilitation services contracted, reconfigured, and were redirected to more remote modes of delivery, and how this affected the capacity of clinicians and patients to participate in rehabilitation. Conclusion: This study demonstrates how changes in provision of rehabilitation during the pandemic could act as a springboard for positive changes. Hybrid models of rehabilitation have the potential to expand the equity of access and reach of rehabilitation within specialist palliative care.